Role for the metalloproteinase ADAM28 in the control of airway inflammation, remodelling and responsiveness in asthma - Bendavid, Guillaume; Hubeau, Céline; Perin, Fabienne; Gillard, Alison; Nokin, Marie-Julie; Carnet, Oriane; Gerard, Catherine; Noel, Agnès; Lefebvre, Philippe; Rocks, Natacha; Cataldo, Didier (Frontiers in Immunology, 2023)
Background Asthma is characterized by morphological modifications of the airways (inflammation and remodelling) and bronchial hyperresponsiveness. Mechanisms linking these two key features of asthma are still poorly understood. ADAM28 (a disintegrin and metalloproteinase 28) might play a role in asthma pathophysiology. ADAM28 exists as membrane-bound and soluble forms and is mainly expressed by lymphocytes and epithelial cells. Methods ADAM28-/- mice and ADAM28+/+ counterparts were sensitized and exposed to ovalbumin (OVA). Airway responsiveness was measured using the flexiVent® system. After sacrifice, bronchoalveolar lavage (BAL) was performed and lungs were collected for analysis of airway inflammation and remodelling. Results The expression of the soluble form of ADAM28 was lower in the lungs of OVA-exposed mice (as compared to PBS-exposed mice) and progressively increased in correlation with the duration of allergen exposure. In lungs of ADAM28-/- mice exposed to allergens, the proportion of Th2 cells among CD4+ cells and the number of B cells were decreased. Bronchial responsiveness was lower in ADAM28-/- mice exposed to allergens and similar to the responsiveness of sham-challenged mice. Similarly, features of airway remodelling (collagen deposition, smooth muscle hyperplasia, mucous hyperplasia) were significantly less developed in OVA-exposed ADAM28-/- animals in sharp contrasts to ADAM28+/+. In addition, we report the first evidence of ADAM28 RNA expression by lung fibroblasts and we unveil a decreased capacity of lung fibroblasts extracted from OVA-exposed ADAM28-/- mice to proliferate as compared to those extracted from OVA-exposed ADAM28+/+ suggesting a direct contribution of this enzyme to the modulation of airway remodelling. Conclusion These results suggest that ADAM28 might be a key contributor to the pathophysiology of asthma.